O feminino em Tieta e Macabéa - Cosme, Gláucia da Silva (2014)
This work, resulting from an analytical and interpretative study of the works Tieta do Agreste, by Jorge Amado, and A hora da estrela, written by Clarice Lispector, aims to investigate how female identity is portrayed in such novels. From this perspective, this study relies on the Critical Theory of Society and Literary Sociology: the first is based on authors such Walter Benjamin and Theodor Adorno; the second is grounded on Antonio Cândido and Alfredo Bosi s theories. Both perspectives emphasize the importance of the historical context for understanding the work, articulating the underlying text with the fictional setting of the narrative elements. Therefore, by analyzing the characters Tieta and Macabea, it will be questioned how female identity is presented in the 1970s. First, it is analyzed the historical context in which the narratives are involved; next it is examined the works and their protagonists and finally it is discussed how female identity is established in these narratives as well as socially, highlighting the main point of rapprochement between the protagonists concerning female roles. At this point, it was sought theoretical support primarily in Nelly Richard, who talks about the fragmentation of the female and points up their exclusion from the conservative culture in large-scale of social spheres. Since female identity is overwhelmed by preconceptions grounded in the Judeo-Christian culture and internalized by society, the women remain at the social margin. By analyzing identity, two disparate personalities can be put together when it comes to female representation. Still, it is discussed the conservative culture that sets society in motion, which when represented from fiction enables to find traces of the 1977 society, year of publication of both narratives. The marks of this period are shown connected to the exclusion of women. The identity, treated as a totalizing element, serves as a point of submersion of women in social spheres. Thus, it is understood that the protagonists as well as women, are looking for space, seeking to legitimacy of their identity.